The Use of Factorial Design for Ferulic Acid Production by Co-Culture - Kamaliah, Abdul Samad; N., Zainol (Elsevier, 2017)
Several factors can influence the use of co-culture for ferulic acid production from banana stem waste. The aim of this study was to analyse factors of temperature, pH, agitation, water-to-substrate ratio, volume of inoculum, fermentation time, and type of co-culture by employing a 24 fractional factorial design (FFD). The results showed the order of contribution effects towards ferulic acid production: pH > type of co-culture > volume of inoculum > agitation > fermentation time > temperature > water-to-substrate ratio. Four factors including pH, agitation, type of co-culture, and volume of inoculum were shown to have significant effects on ferulic acid production. Among the determining factors, the main factor of pH and the interaction of temperature and fermentation time had the strongest effect on ferulic acid production. The result indicated that FFD was useful to improve the ferulic acid production by considering all the interactions of variables involved.